DIFERENCES OF GENDER AND SEXIST PRACTICES IN PHYSICAL EDUCATION: SCIENTIFIC PRODUCTION IN BRAZILIAN PHYSICAL MAGAZINES ABOUT 2000 AND 2008 (Fiep Bulletin - online, 2011)
The gender questions are consolidating in academic reserach, that characterize the importance of studies about this them in the school context. The Physical Education comprehend studies that discuss the importance in the gender relations in the school, so this reserach proposes investigate the production in scientific publications in this area, about gender diferences and sexist practices in Physical Education, also the search of change possibilities in co-educational or mixed. The objetives of research were: a) identify the production in the period about 2000 and 2008, including theoretical and methodologtic elementos that compose the knowledge presented; c) elaborate propositive questions about the issues presented in the reseraches, and d) analyse non yet systematized aspects, proposing theoretical elements that clear/viable the extension of reserch about the theme in the area. This way, it treats about a document analysis of the production about the theme, in Physical Education, in qualitative character. It was found 22 articles that analyse this questions, in 14 magazines, verifying sensible repercussion of theorical reference structuralist and poststructarist reference. The results reveal that studied reserches evidence the discrimination existent of gender in the school and indicate the overcome of dichotomies of sex/gender, but few mencionate the co-education like way of desconstruction in stereotyped relations; the most reveals a scientical-educational dimension to superate the simple execution of Education Pyhisical activities, but they do not realize efective purposes and field experiences that stimulate concret changes in gender relations in shool context. It was evident that efective changes in gender relations are not yet consolidated in the pedagogical propositions and in Physical Education pedagogical practices.
Keywords: Gender; School Physical Education; Sexist Practices